Anti-inflammatory diet and incident peripheral artery disease: Two prospective cohort studies. Issue 6 (June 2022) - Yuan, Shuai; Bruzelius, Maria; Damrauer, Scott M.; Håkansson, Niclas; Wolk, Alicja; Åkesson, Agneta; Larsson, Susanna C.
Summary: Background & aims: Systemic inflammation plays a role in peripheral artery disease (PAD), and therefore, an anti-inflammatory diet may reduce PAD risk. We examined the association between the anti-inflammatory diet and PAD risk by smoking status, a trigger of systemic inflammation. Methods: The study was based on two cohorts of 82 295 Swedish adults aged 45–83 years (38 823 women from Swedish Mammography Cohort and 45 472 men from Cohort of Swedish Men). An anti-inflammatory diet index (AIDI; 0–17 scores) was used to estimate the anti-inflammatory potential of diet. Cox proportional hazards regression models were used to estimate hazard ratios (HRs) with 95% confidence intervals (CIs). Results: Over a median 22-year (interquartile range 7.5 years) follow-up period, 3413 PAD cases were ascertained. Compared with individuals in the lowest quartile of the AIDI (score ≤4), the HR of PAD for those in the highest quartile (score ≥8) was 0.84 (95% CI, 0.74–0.94). The inverse association was observed in current and past smokers but not in never smokers. The HR of PAD comparing extreme quartiles of the AIDI was 0.67 (95% CI, 0.53–0.86) in current smoker, 0.78 (95% CI, 0.63–0.97) in past smoker, and 1.00 (95% CI, 0.82–1.23) in never smokers. Among foods included in AIDI, high consumption of breakfast cereals, chocolate, red wine, and olive/canola oil, and low consumption of processed red meat and organ meats were associated with low PAD risk. Conclusions: The study suggests that adherence to a diet with high anti-inflammatory potential may lower PAD risk, especially in smokers.